Optimization of performance parameters of high-contrast subwavelength grating with high reflectivity for bio-sensing applications - Sharma, Pallavi; Kaler, R.S.; Teotia, Pradeep (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
Highly reflective mirror technologies are majorly required in bio-sensing applications to eliminate complex multiple diffraction orders. In this paper, various grating parameters, i.e. width, thickness, and period are analyzed to get optimized values and high reflectivity for high-contrast subwavelength grating (HCSG) structure. Besides these parameters, polarization modes, angle of incidences, and refractive index have been diversely analyzed to monitor their effects on HCSG structure with respect to reflectivity. The simulation results manifest that the optimized parameters help to achieve the best reflectivity that can be further utilized in bio-sensing applications.
Optica Applicata, Vol. 54, 2024, nr 1, s. 115-122
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; grating parameters; high-contrast subwavelength grating; reflectivity; polarization